(untitled) (Universal International Scientific Journal, 2026)
This article discusses the issue of developing children’s creative skills through the use of authentic materials in the activities of development centers in preschool educational organizations. Authentic materials are interpreted as an important tool for children’s independent thinking, expanding their imagination, and increasing their interest in creative activities. The pedagogical capabilities and practical application mechanisms of development centers are analyzed.